Pengaruh Usia terhadap Tingkat Tekanan Darah, serta Potensi Gangguan Kardiovaskular - Bangkit Ina Ferawati; Mira Setiana (JURNAL KESEHATAN MERCUSUAR, 2023)
Cardiovascular disorders remain a major cause of global morbidity and mortality. The main aim of this study was to identify patterns of association between age and blood pressure and analyze their potential implications for the risk of cardiovascular disorders. The focus of blood pressure analysis is on systolic blood pressure (TDS). The research method involved collecting data on age, blood pressure, and disease history from 42 respondents in Hamlet VI Sonosewu, Kasihan, Bantul. All statistical analyses were performed using Ms. Excel. Statistical analysis is used to describe the pattern of relationships between these variables. The results of the correlation test showed that there is a relationship between age and blood pressure in the sample or population analyzed, which is confirmed by the ANOVA test (p-value: 0.002) and t-analysis test (p-value: 0.002), which produces a p-value < alpha or significance value (0.050). The potential for cardiovascular disorders is known from the results of the chi-square test, the Pearson chi-square statistical value (0,732)< the critical chi-square value (3,840). Based on these results, it can be concluded that in the context of this study. However, age cannot be the main factor determining blood pressure levels and is used as the only risk factor for cardiovascular disorders. Factors such as disease history and lifestyle can be considered as other factors that influence blood pressure levels and the risk of cardiovascular disorders. Blood pressure monitoring and appropriate preventive measures are essential, especially in the elderly age group